Sesamol: A Natural Phenolic Compound with Promising Anticandidal Potential. (9th December 2014) - Ansari, Moiz A.; Fatima, Zeeshan; Hameed, Saif
Abstract : We investigated the antifungal effects of sesamol (Ses), a natural phenolic compound, and exemplified that it could be mediated through disruption of calcineurin signaling pathway in C. albicans, a human fungal pathogen. The repertoire of antifungal activity not only was limited to C. albicans and its six clinical isolates tested but also was against non- albicans species of Candida . Interestingly, the antifungal effect of Ses affects neither the MDR efflux transporter activity nor passive diffusion of drug. We found that C. albicans treated with Ses copies the phenotype displayed by cells having defect in calcineurin signaling leading to sensitivity against alkaline pH, ionic, membrane, salinity, endoplasmic reticulum, and serum stresses but remained resistant to thermal stress. Furthermore, the ergosterol levels were significantly decreased by 63% confirming membrane perturbations in response to Ses as also visualized through transmission electron micrographs. Despite the fact that Ses treatment mimics the phenotype of compromised calcineurin signaling, it was independent of cell wall integrity pathway as revealed by spot assays and the scanning electron micrographs. Taken together, the data procured from this study clearly ascertains that Ses is an effectual antifungal agent that could be competently employed in treating Candida infections.